The curious case of Benjamin Button [videorecording (DVD)] - Fincher, David; Pitt, Brad, 1963-; Blanchett, Cate, 1969-; Henson, Taraji P.; Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Paramount Home Entertainment, 2009)
Daisy Fuller Williams is on her deathbed in a New Orleans hospital the day that Hurricane Katrina hits. At her side is her adult daughter, Caroline. Daisy asks Caroline to read to her aloud from the diary of Daisy's lifelong friend, Benjamin Button. Benjamin's diary recounts his entire extraordinary life. The unusual aspect of his life is that he ages backwards, being born an old man. He is diagnosed with several aged diseases at birth and thus given little chance of survival. He does survive and gets younger with time. Abandoned by Thomas Button, his biological father, after Benjamin's biological mother dies in childbirth, Benjamin is raised by Queenie, a black woman and caregiver at a seniors' home. Daisy's grandmother was a resident, which is where she first met Benjamin. Although separated through the years, Daisy and Benjamin remain in contact throughout their lives, reconnecting in their forties when they finally match up in age. Some of the revelations in Benjamin's diary are difficult for Caroline to read.